EFEKTIVITAS LAYANAN UNTUK ORANG DENGAN GANGGUAN JIWA DI PPSBL MUTMAINNAH LOMBOK TENGAH - Rosiana; Herlina; Kholisus Sa'di (IKIP Siliwangi, 2026)
Mental health services in Indonesia face challenges related to accessibility, the availability of professional personnel, and the unequal distribution of facilities. These service disparities have become increasingly evident, as individuals with mental disorders (IMDs) often receive the least attention or are even neglected. This study aims to examine the effectiveness of services for individuals with mental disorders at the Bina Laras Mutmainnah Social Service Center, Central Lombok. This study employed a descriptive quantitative approach using a survey method. Data were collected through a closed-ended Likert-scale questionnaire consisting of 20 statements based on six indicators: service quality, service satisfaction, service outcomes, improvement of social functioning, improvement of quality of life, and reduction of mental disorder symptoms. The results indicate that the effectiveness of social services for individuals with mental disorders at PPSBL Mutmainnah is categorized as very effective, with an overall achievement of 86.95% of the ideal total score. The highest score was obtained in the service satisfaction indicator (91.50%), while the lowest score was found in the service outcomes indicator (80.80%). Nevertheless, all indicators remained within the effective category. This study presents novelty through the use of six integrated indicators and the direct involvement of service beneficiaries as the main respondents, resulting in findings that are more authentic and contextually grounded. Pelayanan kesehatan jiwa di Indonesia menghadapi kendala dari segi aksesibilitas, ketersediaan tenaga profesional, serta fasilitas yang belum merata. Ketimpangan layanan ini menjadi semakin nyata dimana ODGJ sering kali mendapatkan perhatian terakhir atau bahkan diabaikan. Tjuan penelitian ini untuk Mengetahui Efektivitas Layanan Orang dengan Gangguan Jiwa di Pusat Pelayanan Sosial Bina Laras Mutmainnah Lombok Tengah. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan metode survei. Data dikumpulkan melalui kuesioner tertutup skala Likert yang terdiri dari 20 pernyataan berdasarkan enam indikator: kualitas layanan, kepuasan layanan, hasil layanan, peningkatan fungsi sosial, peningkatan kualitas hidup, dan pengurangan gejala gangguan jiwa. Hasil penelitiannya adalah Hasil penelitian menunjukkan bahwa efektivitas layanan sosial bagi ODGJ di PPSBL Mutmainnah tergolong sangat efektif dengan capaian keseluruhan sebesar 86,95% dari total skor ideal. Indikator dengan nilai tertinggi adalah kepuasan layanan (91,50%), sedangkan nilai terendah terdapat pada indikator hasil layanan (80,80%), namun seluruh indikator tetap berada dalam kategori efektif. Penelitian ini menghadirkan kebaruan melalui penggunaan enam indikator terintegrasi serta keterlibatan langsung penerima manfaat sebagai responden utama, sehingga menghasilkan temuan yang lebih autentik dan kontekstual.